World Pulses Day: on the trail of Yakina the bean - Petit, Raphael; Rubyogo, Jean-Claude; Onyango, Patricia (2021)
The humble bean can make a big impact: the Pan-Africa Bean Research Alliance (PABRA) is using an innovative approach to fight malnutrition, improve food security, stimulate the private sector and empower women in Burundi. In honor of World Pulses Day, we follow the journey of one bean, ‘Yakina’, as it travels from the beanstalk to the mouths of hungry children.